ANALYSIS OF MORBIDITY BY INFECTIOUS DERMATOSIS OF THE POPULATION OF KRASNODAR REGION IN THE LAST 5 YEARS - M. I. Gloozmin; A. G. Shevchenko; E. V. Egorova; M. M. Gloozminа (Кубанский научный медицинский вестник, 2018)
Aim. The aim was to evaluate the epidemiological situation of dermatomycosis and scabies in Krasnodar region, to identify the tendencies and the development trend of the epidemiological situation, as well as the main directions of work retrospectively and in the dynamics of 2013-2017.Materials and methods. Statistical data forms №9, №34 in the last five years, which shape the incidence of contagious dermatoses in Krasnodar region, were used in the study. The morbidity rate of the population of the region is indirectly linked to macroeconomic and social objective and subjective processes in the society.Results. The analysis of the incidence of infectious skin diseases (hereinafter – ISD) shows a negative trend for scabies and major dermatomycosis, with the exception of mycosis of the feet and hands, in the studied five-year period. Structural analysis shows the ratio of sex-age categories of patients with different nosologies: the prevalence of the feet and hands mycoses in adult female patients and microsporia in male children. The link between the number of cases of contagious skin diseases and the territorial gradation of patients was considered. Conclusion. A retrospective analysis of the epidemiological situation of dermatomycosis and scabies in Krasnodar region was conducted. Gender, age and territorial aspects of contagious dermatoses, and the development trends were identified over the analyzed period. The factors contributing to the spread of contagious dermatoses were studied: climatic features of the southern region of the Russian Federation, migration flows, and socio-economic declines. The prospects of preventive work include raising public awareness and joint activities with non-medical services with an emphasis on active detection.